Population-based assessment of barriers for uptake of eye care services among elderly people: Findings from rapid assessment of visual impairment studies from Telangana, India - Srinivas Marmamula; Vijay K Yelagondula; Thirupathi R Kumbham; Satyabrahmanandam Modepalli; Ratnakar Yellapragada; Sanjana Avula; Jill Keeffe (Indian Journal of Ophthalmology, 2022)
Purpose: To report the barriers for seeking eye care among the elderly population aged ≥60 years with avoidable vision impairment (VI) in the South Indian state of Telangana. Methods: A total of 3640 participants aged ≥60 years were recruited using cluster-random sampling. Demographic information, including presenting visual acuity, was measured using the standard Rapid Assessment of Visual Impairment (RAVI) protocol. “Avoidable VI” was considered if the VI was due to cataract or uncorrected refractive error (URE). A detailed interview was conducted using a validated questionnaire to report the barriers for not seeking eye care. Data were analyzed using the Stata statistical software version 14. Results: Prevalence of avoidable VI was 30.2% (95% CI: 28.02–31.06; n = 1102). Among those who noticed decreased vision (n = 1074), only 392 participants (36.4%) reported that they felt the need for seeking eye care. The major barriers for not seeking eye care were: cannot afford the consultation fee and services (42.0%) and no escort (25.7%). Overall, the personal barriers (57.9%) were the major reason for not seeking care, followed by economic barriers (42.0%). No significant difference was reported in barriers between the participants with unilateral and bilateral VI (>0.05). Conclusion: Overall, among the elderly people, personal and economic barriers were the major reason for not seeking eye care. Health care providers and policymakers should focus on newer models of eye care delivery to ensure better accessibility and uptake of care by the elderly people.